Perspectives from students and teachers about the challenges of teaching and learning STEM subjects in Ghana - Akon-Yamga, Gordon; Funkor, Godfried; Tsey, Komla; Kingsford-Adaboh, Robert; Quaye, Wilhemina; Ntewusu, Diana Amoni (Frontiers in Education, 2024)
Ghana has recently renewed its commitment to build a strong Science, Technology and Innovation (STI) base for improved socio-economic development. This commitment hinges on recognizing that the strength of the nation's STI policy depends on the quality of pre-tertiary education and training in science and mathematics to produce a critical mass of young people well-prepared for STEM courses at the tertiary level. However, despite numerous interventions to improve upon STI, Ghana still performs poorly, along with other Sub-Saharan African (SSA) countries with common STI indicators in the Global Innovation Index. Using Ghana as a lens, this paper highlights the challenges in STEM teaching and learning throughout the sub-region. The qualitative research approach was adopted to allow an in-depth exploration of participants' perspectives. Six pre-tertiary schools (three Junior High Schools and Senior High Schools) and the University of Ghana, Legon, were selected due to the availability of their students and teachers to participate in the interviews in Accra, the capital city. The paper argues that, to develop the critical mass of human capital needed for sustainable development, there is a need to improve the performance of students in STEM subjects at the pre-tertiary level. In addition, performance improvement, which is linked to student interest in the study of STEM subjects, should increase the quality of students entering tertiary education institutions. These students will then be trained to meet the quality of human resources needed to run the STI system-a step toward achieving sustainable development this paper recommends the redesign of STEM curriculum at the pre-tertiary level to align with tertiary STEM education as that in turn aligns with Ghana's STI system.